Nonobese diabetic mice express aspects of both type 1 and type 2 diabetes - Chaparro, Rodolfo José (National Academy of Sciences, 2006)
Before the onset of autoimmune destruction, type 1 diabetic patients and an animal model, the nonobese diabetic (NOD) mouse, show morphological and functional abnormalities in target organs, which may act as inciting events for leukocyte infiltration. To better understand these abnormalities, but without the complications associated with lymphocytic infiltrates, we examined genes expressed in autoimmune target tissues of NOD/severe combined immunodeficient (scid) mice and of autoimmune-resistant C57BL/6/scid mice. Our results suggest that the NOD genetic background may predispose them to diabetic complications, including insulin resistance in the absence of high circulating glucose levels and without autoimmune destruction of their β cells. Several of these genes lie within known type 1 and 2 diabetes loci. These data suggest that the NOD mouse may be a good candidate to study an interface between type 1 and type 2 diabetes.